Familial glucocorticoid deficiency presenting with hyperpigmentation, gigantism, and motor development delay: a case report - Uyangoda, Kanchana (J Med Case Rep, 2019)
BACKGROUND: Familial glucocorticoid deficiency is a rare autosomal recessive disorder characterized by isolated glucocorticoid deficiency. Most patients are diagnosed following episodes of hypoglycemia or convulsion. We report the case of an infant with familial glucocorticoid deficiency who presented with hyperpigmentation, gigantism, and motor developmental delay without documented hypoglycemia, convulsion, or circulatory collapse. CASE PRESENTATION: A 10-month-old Sri Lankan Sinhalese baby boy born to consanguineous parents presented with generalized hyperpigmentation and overgrowth since birth. He had marginal gross motor developmental delay. His weight, length, and head circumference were above normal range for his age. Investigations revealed low serum cortisol and high adrenocorticotrophic hormone levels with no cortisol response following adrenocorticotropin stimulation. Serum electrolytes and aldosterone levels were normal. A diagnosis of familial glucocorticoid deficiency was made based on isolated glucocorticoid deficiency, hyperpigmentation, and tall stature. CONCLUSIONS: This case report highlights that glucocorticoid deficiency can present without documented hypoglycemia and circulatory collapse and a high degree of suspicion is needed in diagnosis.